An interactive method for hr training: managers as simulation players - Ertemsir, Esin; Bal, Yasemin (ELSEVIER SCIENCE BV, 2012)
Training and development is one of the most important functions of human resources management. With the increasing importance of human resources value, training and developing employees with essential qualifications and skills have become vital for organizations. There are several HR training methods for various purposes and needs. In this paper, firstly the importance of training and development function of HRM will be discussed and then the traditional and technology based new training methods will be introduced. Finally, simulation method for new generation managers will be investigated in the perspective of the interactivity and visualization advantages. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Prof. Huseyin Uzunboylu.
Keywords: Human Resource Management; Training and Development; Simulations; Education & Educational Research